Correlation of Functional Movement Screen™ and injury in Chinese fencing elite athletes - Zeng, J.; Zhou, L.; Sun, L.; Yin, J.; Liu, K.; Wang, S. (Medicina dello Sport, 2021)
BACKGROUND: Functional movement screen (FMS™) (deep squat [DS], trunk-stability push-up [PU], right and left hurdle step [HS], in-line lunge [ILL], shoulder mobility [SM], active straight leg raise [ASLR], and rotary stability [RS]) has been used to establish normative data and to determine potential injury risk for athletes; however, there are few data in fencing elite athletes. METHODS: The FMS™ was administered to athletes (N.=164) in Chinese national fencing training camp. Medical record data for overuse injury, traumatic injury, and any injury mainly got before FMS™ assessment. Then, data statistics analysis such as descriptive analysis, correlational analysis and regression analysis is done. RESULTS: Statistical significance was set at P=0.05. There were significant correlations between shoulder injury and HS (r=0.173), SM (r=0.345). The PU correlated significantly with both lower back injury (r=0.215) and wrist injury (r=0.156). As for knee injury, it was significantly correlated with RS (r=-0.200). The ankle injury was significantly related to DS (r=0.172). CONCLUSIONS: Based on this study, we can state that injured athletes and non-injured athlete`s FMS™ score have a significant difference in Chinese fencing elite athletes. But given the relatively low correlation between every movement score and injuries on different parts of the body (r<0.30), FMS™ score alone might be insufficient for predicting injury. So, it is difficult to predict fencing athlete`s injuries accurately.